Three-body effects in triplets of capped gold nanocrystals. (18th June 2017) - Bauer, Gernot; Gribova, Nadezhda; Lange, Alexander; Holm, Christian; Gross, Joachim
ABSTRACT: Three-body interactions constitute an important part of the effective potential between nanocrystals (NCs). In this study, molecular dynamics simulations are conducted on gold NCs capped with alkyl thiol ligands in vacuum. Over the course of a simulation performed in two- and three-body systems, we measure the forces acting on the cores of the NCs. These forces are then used to calculate the two- and three-body potentials of mean force (PMF). The influence of the ligand length, the size of the core and the temperature are studied. We find that three-body effects are mainly repulsive. Longer ligand lengths and bigger core sizes further increase the strength of repulsion. According to our simulation data, the three-body contribution is independent of the temperature. Furthermore, we propose an empirical model of the three-body contribution based on the repulsive part of the two-body PMF. Abstract :